Utilization of solid waste materials as alternative fillers in asphalt mixes: A review - Choudhary, Jayvant; Kumar, Brind; Gupta, Ankit (Elsevier Ltd, 2019)
The amendment of producing asphalt mixes with waste materials serves as an avenue to limit the enormous volume of wastes produced from various sources. This also reduce the consumption of naturally mined materials, therefore, minimizing the carbon footprint and pavement industry impact on the environment. This manuscript reviews the wide spectrum of more than 20 well known but under-utilized wastes produced from various sectors (industrial, agricultural, municipal, mining, construction and demolition) which could be utilized as fillers in asphalt mixes. Emphasis was given to the physical and chemical properties of the wastes and their influence on the performance of mixes against primary distresses. This manuscript is likely to motivate researchers and serve as a guideline for adopting non-traditional fillers by highlighting areas likely requiring further research and refinement. Several studies in the recent times have suggested that the use of waste materials in optimum proportion as fillers would lead to production of sustainable asphalt mixes.
Keywords: Asphalt mixes; Flexible pavements; Mineral filler; Recycling; Sustainability; Waste materials